Establish Experimental System of Sheet Metal Hydrostatic Forming for Stepped Cylinder - Nguyen, Thi Thu; Nguyen, Dac Trung; Le, Trung Kien (Old Journal, 2017)
Hydrostatic forming is a deformation method which uses highly-pressed liquid to deform sheet metal following the shape of die. This method has been researched and applied in various industries of manufacturing cars, medicines, chemistry, military, and so on. However, in Vietnam, this method is still new and has not been researched specifically, leading to limited application into real manufacturing. In order to demonstrate specific influence of technological factors on sheet metal hydrostatic forming process, the study on influence of die structure and surface shape on forming ability in sheet metal hydrostatic forming base on the combination of simulation and experiments is needed. Therefore, it is essential that the initial experimental system must be established to research hydrostatic forming process. In this paper, all devices in an experimental system are describes as well as accuracy assurance in experiment are presented.